2013
DOI: 10.2147/vhrm.s50464
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state bioavailability of prescription omega-3 on a low-fat diet is significantly improved with a free fatty acid formulation compared with an ethyl ester formulation: the ECLIPSE II study

Abstract: The systemic bioavailability of free fatty acid (FFA) forms of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) compared with ethyl ester (EE) forms is dependent on the presence of intestinal lipases and is highest during consumption of high-fat meals. Given that patients with cardiovascular disease are advised to reduce dietary fat intake, potentially lowering the bioavailability and therapeutic benefit, the hypothesis that FFA forms provide for higher bioavailability compared with EE forms under lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 17 publications
9
64
0
Order By: Relevance
“…The Food & Drug Administration (2003) defines bioavailability as 'the rate and extent to which the active ingredient (in this case omega-3) is absorbed and becomes available at the site of action' (FDA, 2003). Previous studies have shown that the absorption of free fatty acids from eicosapentaenoic acid (EPA) and DHA depends largely on the presence of intestinal lipases and is generally highest during the consumption of high-fat meals (Offman et al, 2013). Work by the same authors has also shown that higher absorption rates are reflected by increases in blood EPA and DHA levels [demonstrated using area under the curve (AUC) calculations], with study findings showing that the bioavailability of free fatty acid forms of EPA and DHA was significantly higher than the bioavailability from ethyl ester forms, even under low-fat conditions (Offman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Food & Drug Administration (2003) defines bioavailability as 'the rate and extent to which the active ingredient (in this case omega-3) is absorbed and becomes available at the site of action' (FDA, 2003). Previous studies have shown that the absorption of free fatty acids from eicosapentaenoic acid (EPA) and DHA depends largely on the presence of intestinal lipases and is generally highest during the consumption of high-fat meals (Offman et al, 2013). Work by the same authors has also shown that higher absorption rates are reflected by increases in blood EPA and DHA levels [demonstrated using area under the curve (AUC) calculations], with study findings showing that the bioavailability of free fatty acid forms of EPA and DHA was significantly higher than the bioavailability from ethyl ester forms, even under low-fat conditions (Offman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The ECLIPSE II trial also showed significantly greater serum levels of EPA and DHA for those on OM3-CA compared to OM3-EE while on a low-fat diet, however, after a longer time period of 14 days (Figure 1). 41 Furthermore, OM3-CA was more effective than OM3-EE at lowering TG levels (21% vs 8%, p =0.013) at 14 days. This suggests that a greater magnitude of benefit can be expected from OM3-CA compared to older OM3-FA formulations.…”
Section: Introductionmentioning
confidence: 89%
“…In this study, non-HDL-C, TC/non-HDL-C, VLDL, remnant-like particle cholesterol, apoC-III, Lp-PLA 2 , and arachidonic acid (AA) levels were significantly lowered as compared with placebo, but LDL-C was also substantially increased. One advantage is that the availability of the FFA form is up to fourfold higher than from the EE form under low-fat dietary conditions [155][156][157]. In the Epanova combined with a Statin in Patients with hypeRglyerIdemia to reduce non-HDL cholesTerol (ESPRIT) trial, FFA omega-3 was administered to high-risk patients taking statins with TGs between 2.26 and 5.63 mmol/L (200-499 mg/dL); a dose of 2 g/day was found to be effective and well-tolerated for lowering non-HDL-C and TGs, as opposed to a higher dose of 4 g/day of other forms [157].…”
Section: Omega-3 Polyunsaturated Long-chain Fatty Acidsmentioning
confidence: 99%